Impacto social de las microfinanzas en los microempresarios de la ciudad de Loja, periodo 2010-2013 - Jiménez Mendoza, Liliana Katherine (2015)
Microfinance is a tool that offers multiple opportunities for economic and social development for people in countries that are developing, by financing productive projects that can generate income to meet household needs. With this background the present study to analyze in general the contribution of microfinance in Ecuador and specifically the benefits received by microentrepreneurs City Loja, during the period 2010-2013 was performed. Has been taken as reference information for entrepreneurs registered in the database of the Provincial Directorate of the Ministry of Industry and Productivity of Loja; while on the supply side, reference to Segment Four microfinance institutions controlled by the Superintendencia de Economía Popular y Solidaria and regulated by the Superintendencia de Bancos due to the availability of information provided by these agencies entities is done.